2010
DOI: 10.1097/iop.0b013e3181d8e150
|View full text |Cite
|
Sign up to set email alerts
|

Abobotulinum Toxin A (Dysport) and Botulinum Toxin Type A (Botox) for Purposeful Induction of Eyelid Ptosis

Abstract: Chemodervation with abobotulinum toxin A (Dysport) and botulinum toxin type A (Botox) is finding an expanding role in functional and cosmetic cases. We describe the use of chemodenervation with abobotulinum toxin A for functional corneal protection in two cases and botulinum toxin type A for facial symmetry after Bell's palsy in one patient. The first case is a 75-year-old female with a nonhealing corneal erosion in her right eye secondary to epithelial basement membrane corneal dystrophy who underwent injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
6
0
4
Order By: Relevance
“…11 In the treatment of lagophthalmos, in addition to the supporting measures mentioned previously, abobotulinum toxin A can be used to purposefully cause chemodenervation of Muller's muscle and the levator palpebrae superioris and may be useful in nonpermanent facial paralysis as it is reversible, provides temporary corneal protection, and obviates the need for surgery. 2,12 Injection of hyaluronic acid into the upper eyelid prelevator aponeurosis region and/or pretarsal region, which demonstrated improvement in lagophthalmos and exposure keratopathy in nine patients with minor morbidity, may be useful as a temporizing measure while awaiting facial nerve function to return or for poor surgical candidates. 13 Further surgical management includes static loading of the upper eyelid with rigid weights to provide gravity-assisted closure.…”
Section: Eyementioning
confidence: 99%
“…11 In the treatment of lagophthalmos, in addition to the supporting measures mentioned previously, abobotulinum toxin A can be used to purposefully cause chemodenervation of Muller's muscle and the levator palpebrae superioris and may be useful in nonpermanent facial paralysis as it is reversible, provides temporary corneal protection, and obviates the need for surgery. 2,12 Injection of hyaluronic acid into the upper eyelid prelevator aponeurosis region and/or pretarsal region, which demonstrated improvement in lagophthalmos and exposure keratopathy in nine patients with minor morbidity, may be useful as a temporizing measure while awaiting facial nerve function to return or for poor surgical candidates. 13 Further surgical management includes static loading of the upper eyelid with rigid weights to provide gravity-assisted closure.…”
Section: Eyementioning
confidence: 99%
“…There are two case series of therapeutic chemodenervation with Botox of these muscles comprising three and 10 patients, respectively. 76,77 Both showed that Botox administration is beneficial in preventing damage as well as healing of the cornea [4]. In addition, there is one case series of 30 patients showing Botox to reduce synkinesis in aberrant facial nerve regeneration following facial nerve paresis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Prosigne Ò (Lanzhou Institute of Biological Products) and Botox Ò (Allergan, Inc., Irvine, CA) have 1:1 dose equivalence and have equal clinical effect, efficacy, tolerability, and safety. 20,21 The dose determined for this study was not the same Dysport Ò (Ipsen Slough, UK/Galderma, Paris, France) dose of 33.3 U per point of application used in the treatment of blepharospasm in one dog 15 or 24 U that has also been used to induce protective ptosis in humans 22 because there is no bioequivalence between Dysport Ò (Ipsen Slough, UK/Galderma, Paris, France) and Prosigne Ò (Lanzhou Institute of Biological Products). Reports state that a simple doseconversion factor is not applicable because units of different serotype A toxins are not interchangeable.…”
Section: Discussionmentioning
confidence: 99%